On Some New Fixed Point Results with Applications to Matrix Difference Equations - Marwan Amin Kutbi; Jamshaid Ahmad; Muhammad Imran Shahzad (Journal of Mathematics)
The aim of this article is to discuss the convergence of iterative sequences of the Prešić type involving new classes of operators satisfying Prešić type Θ-contractive condition in the context of metric spaces. Some examples are also provided to show the significance of the investigation of finding fixed points. Some convergence results for a class of matrix difference equations will be derived as application.